THE IMPACT OF THE ECOLOGICAL CRISIS IN THE ARAL SEA REGION ON THE PROGRESSION OF CHRONIC KIDNEY DISEASE: A COMPREHENSIVE ANALYSIS OF TRADITIONAL AND NON-TRADITIONAL RISK FACTORS (6-MONTH OBSERVATIONAL STUDY) (Modern American Journal of Medical and Health Sciences, 2025)
In the context of the ecological crisis in the Aral Sea region (dust storms, water mineralization, and intense insolation), a study was conducted to investigate the risk factors for the development and progression of chronic kidney disease (CKD). At the first stage, 500 residents of the region (aged 25–65) underwent a screening questionnaire using a modified scoring system that included both traditional risk factors (arterial hypertension, diabetes mellitus, obesity, smoking) and region-specific "non-traditional" factors (proximity to the Aral Sea, drinking water source, level of insolation). In 115 patients with high or moderate risk (based on the questionnaire), CKD stages II–IV were verified, and a 6-month follow-up was initiated with monitoring of GFR and ultrasound. In parallel, data from 217 CKD patients from primary healthcare settings were analyzed. The results showed.